Covid-19 Vaccination in News Construction kompas.com and cnbc.com - Eli Purwati; Ayub Dwi Anggoro; Krisna Megantari (ARISTO, 2022)
The dynamics of handling COVID-19 in Indonesia is entering a new phase, namely vaccination. There is a phenomenon that is widely discussed in the community about the pros and cons of the effectiveness of the Sinovac and AstraZeneca vaccines. The media skillfully writes various news points of view related to government policies in terms of vaccination. In this case, the news delivered by kompas.com media on March 10, 2021 and cnbcindonesia.com on March 9, 2021 about the efficacy of vaccination is interesting to study.  The two media frame the Vaccine news differently, The objective of this study is to compare the news content of the two media. This study applies a qualitative approach and Robert Etmant's framing analysis model. According to the results of research on news at kompas.com, the elaboration of the explanation about the AstraZeneca vaccine is so complete and detailed, but it is in contrast to the explanation elaborated on the Sinovac vaccine. On the other hand, in the news on cnbcindonesia.com, the elaboration on the use of technology is described in a balanced way. It was concluded that kompas.com wrote a balanced report on the information process while cnbcindonesia.com wrote it in a balanced way in the information process.